Psychotic Disorders An Update - Durbano, Federico (IntechOpen, 2018)
In this book, with the involvement not only of clinical psychiatrists but also of neurobiologists, specific issues of psychotic disorders (mainly schizophrenia and mood disorders) are reviewed. The focus of attention ranges from therapeutics to the new frontiers of epigenetics. A special focus is on the individual reactions to psychosis (ranging from psychological ones to treatments and neurobiological basis). Because of the rapid development of neurosciences, which are showing common underling factors to different phenotypical expressions of mental illness, we are facing an enormous growth of biological data, which is not always easy to interpret. The risk is to forget that we are relating to other individuals, with their stories, and, most of all, with their environmental resources and interactions. The contributions to this book will range from individual experience (a personal history of illness) through some aspects of individual management of illness (insight), from correct use of available psychosocial resources to the environment-gene relationships (epigenetics).